A New Russian Waste Management Installation - Griffith, Andrew; Engxy, Thor; Endregard, Monica; Schwab, Patrick; Nazarian, Ashot; Krumrine, Paul; Backe, Steinar; Gorin, Stephen; Evans, Brent (WM Symposia, Inc., 2003)
The Polyarninsky Shipyard (sometimes called Navy Yard No. 10 or the Shkval Shipyard) has been designated as the recipient for Solid Radioactive Waste (SRW) management facilities under the Arctic Military Environmental Cooperation (AMEC) Program. The existing SRW storage site at this shipyard is filled to capacity, which is forcing the shipyard to reduce its submarine dismantlement activities. The Polyarninsky Shipyard Waste Management Installation is planned as a combination of several AMEC projects. It will have several elements, including a set of hydraulic metal cutting tools, containers for transport and storage, the Mobile Pretreatment Facility (MPF) for Solid Radioactive Waste, the PICASSO system for radiation monitoring, and a Waste Storage Facility. Hydraulically operated cutting tools can cut many metal items via shearing so that dusts or particulates are not generated. The AMEC Program procured a cutting tool system, consisting of a motor and hydraulic pumping unit, a 38-mm conduit-cutting tool, a 100- mm pipe-cutting tool, and a spreading tool all mounted on a wheeled cart. The vendor modified the tool system for extremely cold conditions and Russian electrical standards, then delivered the tool system to the Polyarninsky shipyard. A new container for transportation and storage of SRW and been designed and fabricated. The first 400 of these containers have been delivered to the Northern Fleet of the Russian Navy for use at the Polyarninsky Shipyard Waste Management Installation. These containers are cylindrical in shape and can hold seven standard 200-liter drums. They are the first containers ever certified in Russia for the offsite transport of military SRW. These containers can be transported by truck, rail, barge, or ship. The MPF will be the focal point of the Polyarninsky Shipyard Waste Management Installation and a key element in meeting the nuclear submarine dismantlement and waste processing needs of the Russian Federation. It will receive raw waste in various conditions, treat it, package it in standard 200-liter drums, and load these drums into the new transportation and storage containers. The MPF has been designed, fabricated, and assembled at the fabrication site, the Zvezdochka Shipyard. It passed a demonstration test in September 2002. The entire MPF has been disassembled into its transportable modules, which are currently stored at the Zvezdochka Shipyard. In the spring of 2003, the MPF modules will be transported to the Polyarninsky Shipyard, where they will be reassembled and the facility will be cold tested. The site preparation work is already under way for the installation at the Polyarninsky Shipyard. An automatic radiation monitoring system, PICASSO-AMEC, has been developed and will be installed at Polyarninsky Shipyard as one of the elements of the installation. The radiation monitoring system is based on the software package PICASSO-3, developed by the Institute for Energy Technology in Norway. Treated waste f rom the MPF will require safe and secure storage. The Waste Storage Facility will be connected to the MPF, and it will be large enough to store all 400 of the new containers. Incoming waste boxes in overpacks will enter one part of the storage facility on trucks. Then they will be inspected and transferred into the MPF through the receiving area. Drums of processed waste in containers will be removed from the MPF and stacked in another part of the storage facility via a bridge crane. This facility will be designed and construction will begin during the winter of 2002/2003.